Fanaticism and the Zhuangzi: The Discursive Conditions for Unhealthy Commitments - Daniel Sarafinas (Religions)
This article utilizes the Zhuangzi’s critical approach to language to expand contemporary discourse on the philosophy of fanaticism beyond the conceptual categories derived from European Enlightenment-era critiques of religious and political fanaticism. Recognizing some of the problematic tendencies that stem from the method of comparison itself, an articulation of a post-comparative paradigm is proposed, which emphasizes approaches from non-Western sources that are not predicated upon the comparison of similarities or differences with Western sources. The main body of this article explicates the Zhuangzi’s critiques of a linguistically and discursively conditioned fanaticism. These critiques focus on the following: (1) the interdependence of binary linguistic terms that constitute shifei discourse; (2) semiotic chains of cascading distinctions that confound attempts to ground shifei judgements; and (3) the relationship between unhealthy forms of language, thought, and anxieties and a discursively conditioned fanaticism. This article concludes with a brief reflection on how the Zhuangzi’s critiques of a linguistically and discursively conditioned fanaticism might open discourse on the philosophy of fanaticism in more ways than by merely adding a token Chinese voice.